Balancing personal wishes and caring capacity in future planning for adults with an intellectual disability living with family carers. (September 2019) - McCausland, Darren; Brennan, Damien; McCallion, Philip; McCarron, Mary
Most people with intellectual disabilities (IDs) live at home with family, and most carers and care recipients wish to continue this arrangement. However, despite worry about what will happen when carers are unable to continue caring, most families do not plan for the future. The Future Care Road Map (FCRM) pilot study sought to enhance future care planning for families of adults with ID. Twelve families were facilitated through the FCRM process to establish future care plans, including future living and care arrangements. The pilot successfully improved future planning, but readiness of families and facilitation were important to outcomes. Continued care within the family was the most common future wish of care recipients. However, caring capacity emerged as a pervasive theme. Ultimately, it may be the capacity of the family, services or individual with ID themselves to provide future care which determines how feasibly future wishes translate into future plans.